Chapter Commento alla traduzione. Traduttori non sempre traditori - Tylusinska-Kowalska, Anna (Studi di Traduzione Letteraria Lusofona, 2020)
Starting from a statement of Pirandello concerning the art of translation, the essay aims to reflect on the concept of translator and on the frequent false attribution of traitor. In addition to this, the essay focuses on the Italian translation of the literary work of Adalberto Alves A presença dos dias / La presenza dei giorni.